International Publication Trends in Low Back Pain Research: A Bibliometric and Visualization Analysis - Huang, Fan; Zheng, Beisi; Wu, Cunshu; Zhao, Siyi; Xu, Yuanyue; Li, Ziyuan; Huang, Chuyu; Fan, Zhiyong; Wu, Shan (Frontiers in Public Health, 2022)
Background Although there is a growing research base on low back pain, the bibliometric literature related to it is deficient. The aim of this study was to conduct a bibliometric and visualization analysis of low back pain and to provide a broad view of the current trends in LBP research and a potential guide in this discipline. Methods The authors searched the Web of Science to extract publications regarding low back pain, and found a total of 12,249 publications during a period of 22 years, among which 12,242 were eligible. We classified and analyzed publications such as total citations, average citations per item, H-index, research types, countries/regions, institutions, and journals using standard bibliometric indicators. Bibliometric approaches (VOSviewer1.6.13 and CiteSpace 5.8.3) were also available for gathering information and explore the trends of research. Results Conspicuously, over the past 22 years, an increasing number of scholars have specialized in the research of LBP, exerting the boom in articles. The largest number of document type was that of articles. Under modern conditions, regional distinction existed in the research of low back pain and developed countries preceded others. Research individuals and institutions were preoccupied by respective aspects. Visualization analysis provided objective information for potential collaborators and cooperative institutions. Furthermore, most burst keywords varied during different periods. Conclusions The map of research on LBP obtained by our analysis is expected to help researchers to efficiently and effectively explore LBP.